Prediction of characteristics of cement stabilized earth blocks using non-destructive testing: Ultrasonic pulse velocity and electrical resistivity - Sathiparan, N.; Jayasundara, W.G.B.S.; Samarakoon, K.S.D.; Banujan, B. (Elsevier, 2023)
The quality monitoring procedure is so tricky in cement-stabilized earth masonry buildings that it is typically avoided. As a potential means of enhancing the aforementioned quality control, the current study investigates some statistical analyses regarding the relationship between two non-destructive tests (ultrasonic pulse velocity and electrical resistivity) and the density and compressive strength of cement-stabilized earth blocks (CSEB). Blocks with ten different cement-soil mixes were cast and tested considering three soil types and various cement- to-soil ratios. Correlation analysis was done to determine the best relationship between the properties of stabilized earth blocks (density, dry compressive strength and saturated compressive strength) and non-destructive measurements (ultrasonic pulse velocity and electrical resistivity). To adequately describe the variability in compressive strength using both types of non-destructive testing, univariate and multivariate regression models were set up. When multivariate models (using a combination of UPV and electrical resistivity) were used to predict the dependent variable showed a stronger correction between properties of CSEBs and non-destructive measurements. It is shown that a combination of UPV and electrical resistivity can be used to qualitatively evaluate the properties of CSEBs for better accuracy.
Keywords: Stabilized soil blocks; Compressive strength; Ultrasonic pulse velocity; Electrical resistivity